2015
DOI: 10.5465/ambpp.2015.13595abstract
|View full text |Cite
|
Sign up to set email alerts
|

Always on my mind: The impact of relational ambivalence on rumination upon supervisor mistreatment

Abstract: 1Always on my mind: The impact of relational ambivalence on rumination upon supervisor mistreatment ABSTRACTOften viewed as a self-regulatory impairment (Thau & Mitchell, 2010), rumination describes the repeated pondering of an offense (Caprara, 1986). The current study predicts that employees high in relational ambivalence with supervisors, or who "maintain both a positive and negative attitude toward their supervisor," are more likely than those in positive or negative relationships to ruminate over a superv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 63 publications
(84 reference statements)
0
6
0
Order By: Relevance
“…Similarly, organizational research has supported the salience of sense-making processes when employees feel harmed by their organization (Cole, Bernerth, Walter, & Holt, 2010;Lian et al, 2014;Thau & Mitchell, 2010). Third, and relatedly, psychological contract violation is likely to trigger rumination (Ingram, 2015), and employees need to cope with their disruptive ruminative thoughts. Scholars have repeatedly found that mistreatment can lead to employee rumination (Baranik, Wang, Gong, & Shi, in press;Rafaeli et al, 2012;Wang, Bowling, Tian, Alarcon, & Kwan, in press).…”
Section: Theory and Hypotheses Developmentmentioning
confidence: 97%
“…Similarly, organizational research has supported the salience of sense-making processes when employees feel harmed by their organization (Cole, Bernerth, Walter, & Holt, 2010;Lian et al, 2014;Thau & Mitchell, 2010). Third, and relatedly, psychological contract violation is likely to trigger rumination (Ingram, 2015), and employees need to cope with their disruptive ruminative thoughts. Scholars have repeatedly found that mistreatment can lead to employee rumination (Baranik, Wang, Gong, & Shi, in press;Rafaeli et al, 2012;Wang, Bowling, Tian, Alarcon, & Kwan, in press).…”
Section: Theory and Hypotheses Developmentmentioning
confidence: 97%
“…Though this research does not provide a precise estimation of relationships that are ambivalent, in studies of undergraduate and community samples, individuals report that ambivalent ties frequently define their social networks (e.g., spouse, coworkers, family members, friends), with comparable numbers of positive and ambivalent relationships and more ambivalent than negative relationships . These frequencies likely translate to the workplace: Individuals experience mixed feelings about their work groups and organizations (Kreiner & Ashforth, 2004;Sluss & Ashforth, 2007), mentors may feel both proud of and threatened by their protégés (Eby, Butts, Durley, & Ragins, 2010), and employees feel ambivalently about their customers (Pratt & Doucet, 2000), managers (K. Ingram, 2015;Lee, Martin, Thomas, & Guillaume, 2015), colleagues (Zou & Ingram, 2013), and friends (P. Ingram & Zou, 2008). For instance, Pratt and Doucet (2000) describe how employees expressed feeling ambivalently toward managers who are demanding but also indispensable sources of support and toward customers whom they enjoy helping but who also slow their productivity.…”
Section: Ambivalent Relationshipsmentioning
confidence: 99%
“…How about behavior, would behavior ambivalence be more powerful than other types? (Casciaro and Lobo, 2005, 2015. Third, the positives outcomes mainly come from ambivalent leader behavior, such as paradoxical leadership, visionary plus empowering leadership, and leader humility plus narcissism.…”
Section: Discussionmentioning
confidence: 99%
“…Inconsistency in decision making (De Cremer, 2003) ----Multiplex tie (4) (5) (6) LMX ambivalence (Lee et al, 2019); Relational ambivalence (Guarana and Hernandez, 2015;Ingram, 2015) --Behavior…”
Section: Type Of Ambivalent Leader-follower Relationshipsmentioning
confidence: 99%